TOWARDS THE INTERNATIONAL FINANCIAL REPORTING STANDARD ADOPTION: A WILL OR A CONSTRAINT - Ahmadi, Ali (Universitas Pakuan, 2025)
ABSTRACTThis study aims to apply the adoption of Internatisonal Financial Reporting Standard (IFRS) which is one of the newest and most debated terms in accounting research in the last two decades. This study is a descriptive study with data sources derived from articles, accounting standard statements and other primary sources. The study result show the transition to international accounting standards (IFRS) has brought significant changes to financial reporting, including social reporting and the level of conservatism. While IFRS improves transparency and investment efficiency, challenges remain in balancing compliance with global standards with the need for sustainability-oriented reporting. This study contributes to the growing literature that investigates the adoption of IFRS in the new global economic order, societal consistency, and the relationship between accounting conservatism and investment policy effectiveness. One of the main objectives is to improve investors' perceptions of the value of assets acquired while replacing the concept of